Infrared polarimetry of the southern massive star-forming region G333.6-0.2 - Fujiyoshi, T; Smith, C; Wright, C; Moore, T; Aitken, D; Roche, P (2001)
We present 8-13 μm spectropolarimetry, and 12- and 2-μm imaging polarimetry of the southern massive star-forming region G333.6-0.2. Spectropolarimetry measurements show that the polarization observed towards the nebula contains a mixture of both absorptive and emissive polarizations. Model fitting to the spectra indicates that the temperature of the mid-infrared emitting dust grains is generally ∼200 K and the optical depth of the absorbing dust at 9.7 μm is ∼ 1.5. Fits are also made to the polarimetry spectra, which show a reasonably constant peak absorptive polarization (∼3.4 per cent at 43°) across the face of the H II region. This absorptive polarization position angle is consistent with that found by the 2-μm imaging polarimetry (38° ± 6°) and is most likely due to the Galactic magnetic field local to G333.6-0.2. When the absorptive polarization is subtracted from the 12-μm polarization image, the emissive polarization pattern that is intrinsic to the star-forming region is revealed. A probable magnetic field configuration implied by the intrinsic polarization suggests star formation initially influenced by the Galactic magnetic field which is eventually perturbed by the star formation process.